Política de familia en América del Sur: un análisis comparado - Leidi Viviana Moreno-Parra; Carmen Verde-Diego; Rubén González-Rodríguez (Revista Iberoamericana de Estudios de Desarrollo)
In this study, it is identified the approach to family in social policies in different South American countries. A review of the literature and an analysis of the constitutions, social policies, plans, programs, projects, and national services related to the family have been carried out through institutional websites. The results are presented by country and comparative analysis. They show social policies designed for a «normative» family —nuclear, two-parent, and heterosexual— as a rights-bearing subject, and its protection in all the countries but in different degrees. With a few exceptions, family diversity is not included; the policies are not directed toward families as a set, but at their different members, and attention is broken down toward those who are considered the most vulnerable, such as infants, women, seniors, people with disabilities, and/or based on social issues such as poverty, health, schooling, gender-based violence, rural isolation, or indigenous issues.